Deletion of TLX and social isolation impairs exercise‐induced neurogenesis in the adolescent hippocampus. Issue 1 (13th October 2017) - Kozareva, Danka A.; O'Leary, Olivia F.; Cryan, John F.; Nolan, Yvonne M.
Abstract: Adolescence is a sensitive period of neurodevelopment during which life experiences can have profound effects on the brain. Hippocampal neurogenesis, the neurodevelopmental process of generating functional new neurons from neural stem cells, occurs throughout the lifespan and has been shown to play a role in learning, memory and in mood regulation. In adulthood it is influenced by extrinsic environmental factors such as exercise and stress. Intrinsic factors that regulate hippocampal neurogenesis include the orphan nuclear receptor TLX (Nr2e1) which is primarily expressed in the neurogenic niches of the brain. While mechanisms regulating adult hippocampal neurogenesis have been widely studied, less is known on how hippocampal neurogenesis is affected during adolescence. The aim of this study was to investigate the influence of both TLX and isolation stress on exercise‐induced increases in neurogenesis in running and sedentary conditions during adolescence. Single‐ (isolation stress) wild type and Nr2e1 ‐/‐ mice or pair‐housed wild type mice were housed in sedentary conditions or allowed free access to running wheels for 3 weeks during adolescence. A reduction of neuronal survival was evident in mice lacking TLX, and exercise did not increase hippocampal neurogenesis in these Nr2e1 ‐/‐ mice. This suggests that TLX is necessary for the pro‐neurogenic effects of exercise during adolescence. Interestingly, although social isolation during adolescence did not affect hippocampal neurogenesis, it prevented an exercise‐induced increase in neurogenesis in the ventral hippocampus. Together these data demonstrate the importance of intrinsic and extrinsic factors in promoting an exercise‐induced increase in neurogenesis at this key point in life.